PENILAIAN RISIKO DAN STRATEGI MITIGASI PADA RANTAI PASOK INDUSTRI BATIK TULIS ORGANIK : Studi Kasus - Titisari, Manik Ayu; Pramana, Yanatra Budi; Nafiuddin, Muhammad Rizky (Heuristic, 2024)
The organic batik tulis (hand-written batik) product is a new challenge in the batik industry since it uses natural dyes, which aligns with their mission not to damage the environment. It is vital to assess risks and mitigation strategies in the supply chain so that companies are aware and can anticipate the impact of these risks. This research aimed to identify and evaluate activities that could cause risks along the supply chain route of the organic batik tulis industry, determine risk priorities, and formulate mitigation strategies using the Failure Mode Effect Analysis (FMEA). The research results would show risky supply chain activities involving the government, suppliers, companies, and distributors. Furthermore, activities with the highest risk would be determined, as well as developing a mitigation strategy prioritizing raw materials, technological modifications, resources, and infrastructure. The research results show 20 risk activities in the organic batik tulis supply chain, comprising six risks from suppliers, seven from processes, and seven from distributors. The highest risk was in the (1) process, which was the risk of the impact of natural dye waste on the water environment, and in the (2) distributors, which was the risk of damaged packaging. The mitigation strategy will focus on technology, human resources, and infrastructure.